PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERAHADAP HASIL BELAJAR BAHASA INDONESIA DI KELAS IV SD NEGERI 55 PALEMBANG - Pallaya, Dina; Murniviyanti, Liza; Anisah Utami, Sonia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Think Pair Share learning model on the Indonesian language learning outcomes of fourth-grade students of SD Negeri 55 Palembang on the material of facts and opinions. This study uses a quantitative approarch with a true experimental method using a posttest only control group design. The research sample consisted of class IV A as an experimental class that received Think Pair Share learning and class IV B as a control class that used conventional learning. Data were collected through a learning outcome test in the form of essay questions and analyzed using normality tests, homogeneity tests, and hypothesis tests with Independents Sample T-Test. The results showed that the data were normally distributed an gomogeneous with a significance value of 0.200 for the experimental class and and 0.169 for control class and 0.194 for the homogeneity test. The average learning outcomes of the experimental class was 90.88, higher than the control class at 71.48. The results of the hypothesis tests showed a significance value (2-tailed) of 0.000 < 0.05, thus Ho was rejected and Ha was accepted. Based on the research results. Thus, the Think Pair Share learning model had a significant effect on the Indonesian language learning outcomes of fourth-grade students at SD Negeri 55 Palembang and was more effective than conventional learning